Quality management systems for your in vitro fertilization clinic's laboratory: Why bother? - Jan I Olofsson; Manish R Banker; Late Peter Sjoblom (Wolters Kluwer Medknow Publications, 2013)
Several countries have in recent years introduced prescribed requirements for treatment and monitoring of outcomes, as well as a licensing or accreditation requirement for in vitro fertilization (IVF) clinics and their laboratories. It is commonplace for Assisted Reproductive Technology (ART) laboratories to be required to have a quality control system. However, more effective Total Quality Management systems are now being implemented by an increasing number of ART clinics. In India, it is now a requirement to have a quality management system in order to be accredited and to help meet customer demand for improved delivery of ART services. This review contains the proceedings a quality management session at the Indian Fertility Experts Meet (IFEM) 2010 and focuses on the creation of a patient-oriented best-in-class IVF laboratory.